Attending to Screens and Screenness: Guest editorial for special issue of Encounters - Ross Winthereik,Brit; A. Lutz,Peter; Suchman, Lucy; Verran, Helen (STS Encounters, 2011)
This special issue is a follow up on a PhD course entitled “Framing Screens: Knowledge, Interaction and Practice” held at the IT University of Copenhagen in the fall of 2010. Course participants from a variety of disciplines and countries joined the senior faculty who served as midwives for the births of new understandings and conceptualizations of screens.